The characterisation of monoclonal antibodies against haemopoietic cells: comparison of an immunoperoxidase method with fluorescence activated cell sorting. - Swirsky, D; Watt, S; Gilmore, D; Hayhoe, F; Waldmann, H (1983)
Nucleated cells from normal human peripheral blood and bone marrow have been analysed with 2 rat monoclonal antibodies of known specificity, one (YAML 555.6.6) directed against the P28,33 complex (anti-HLA-DR), and the other (YAML 501.4.4) directed against leucocyte common antigen (anti-LCA). The patterns of reactivity with an indirect immunoperoxidase method on fixed smeared cells were in close agreement with those obtained with a fluorescence activated cell sorter. A further new monoclonal antibody of unknown antigen specificity (YAML 537.2) reacts with an intracellular antigen present in neutrophils and their precursors from the promyelocyte stage onwards, megakaryocytes, and a proportion of monocytes, but not with eosinophils, nucleated red cells or lymphocytes. This reactivity could not be demonstrated using the fluorescence activated cell sorter. The immunoperoxidase method allows the identification of individual positive and negative cells and therefore provides a method of identifying minor reactive and non-reactive cell populations in a heterogeneous cell sample such as normal bone marrow. Cytoplasmic binding sites can be differentiated from membrane binding.